PENGARUH KETERLIBATAN BUDAYA TERHADAP KEUNGGULAN OPERASIONAL UMKM KABUPATEN BANDUNG - Eka Ludiya; Andri Irawan (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
SMEs are part of the business world and become one of the important factors in facing theeconomic crisis experienced by Indonesia in 1998 is now getting more attention from the government asa solution in dealing with and solving social problems.The goal to be achieved in this research is to measure and know how big influence of culturalinvolvement to operational excellence at SMEs Food and Beverage at Regency of bandung. This typeof research is used to examine causal relationships that are not manipulated or treated. The populationin this study type unknown population number while the sample size taken is 100 respondents. Thesampling method used by the researcher is nonprobability sampling by accidental sampling. Testinstrument instrument using validity and reliability test. The analysis tool used is SEM Pls. Datadiscussion using SEM Pls concludes that cultural involvement gives 46% influence to operationalexcellence on SMEs Food and Beverage in Bandung regency.